Short-term effects of ambient air pollution on emergency department visits for urolithiasis: A time-series study in Wuhan, China - Xu, Haoyue; Liu, Yaqi; Wang, Jianing; Jin, Xiaoqing (Frontiers in Public Health, 2023)
Background: Previous studies have explored the correlation between short-term exposure to air pollution and urinary system diseases, but lack of evidence on the correlation between air pollution and urolithiasis. Methods: Daily data of emergency department visits (EDVs), concentrations of six air pollutants (SO2, NO2, PM2.5, PM10, CO, and O3) and meteorological variables were collected in Wuhan, China, from 2016 to 2018. And a time-series study was conducted to investigate short-term effects of air pollutants on urolithiasis EDVs. In addition, stratified analyses by season, age and gender were also conducted. Results: A total of 7483 urolithiasis EDVs were included during the study period. A 10-μg/m3 increase of SO2, NO2, PM2.5, CO, PM10, and O3 corresponded to 15.02% (95% confidence interval [CI]: 1.69%, 30.11%), 1.96% (95% CI: 0.19%, 3.76%), 1.09% (95% CI: -0.24%, 2.43%), 0.14% (95% CI: 0.02%, 0.26%), 0.72% (95% CI: 0.02%, 1.43%), and 1.17% (95% CI: 0.40%, 1.94%) increases in daily urolithiasis EDVs. Significant positive correlations were observed between SO2, NO2, CO, and O3 and urolithiasis EDVs. The correlations were mainly among females (especially PM2.5 and CO) and younger people (especially SO2, NO2,and PM10) but the effect of CO was more obvious in elders. Futhermore, the effects of SO2 and CO were stronger in warm seasons, while the effects of NO2 were stronger in cool seasons. Conclusion: Our time-series study indicates that short-term exposure to air pollution (especially SO2, NO2, CO, and O3) was positively correlated with EDVs for urolithiasis in Wuhan, China, and the effects varied by season, age and gender.